Isolamento, identificação e seleção de Bacillus spp. para o biocontrole de fitopatógenos do arroz - Nascimento, Ivaneide de Oliveira (2009)
Fungal diseases are one of the main factors that affect the productivity and performance in rice crops, not only in the irrigated rice system but also in the high lands and lowlands ones. The utilization of Bacillus spp. as biological control agents, inside an integrated management, presents efficiency, besides security to the farmers and the environment. Therefore, this research aimed obtains and identify Bacillus ssp. from municipalities of Maranhão, evaluating the in vitro antagonism related to the mycelial growth of Pyricularia grisea, and the effect of seed microbiolization in rice seeds, Bonança variety, in the incidence and reduction of plant pathogens in seeds and plants. Firstly, it was collected healthy rice leaves in crops from ten municipalities, allowing the Bacillus ssp. isolation and the identification through biochemical tests. Tests were made to select a standard isolate to evaluate the Point, One Central Streak and Circle methods, to choose one to test eighteen isolates as for inhibition of the pathogen mycelial growth. In those tests it was adopted the completely randomized experimental design. Subsequently, seed rice health, Bonança variety, was evaluated in Blotter Test and the effect of microbiolization with Bacillus spp., in saline solution with concentration adjusted in OD540 = 0,5, in the incidence and reduction of pathogens in seeds and plants. The incidence and control of pathogens in seeds were evaluated at seven days and in greenhouse at seven and fourteen days, using 100 plants/time. According to the results twenty-one isolates were obtained, distributed among the species B. licheniformes (10 %), B. polymyxa (25 %), B. macerans (5 %), B. lentus (15 %), B. pentothenticus (15 %), B. pumilus (10 %), B. cereus (25 %) e B. stearothermophilus (5 %). The mycelial growth control methods that presented greater percentage of inhibition were Circle and One Central Streak methods. The Circle method enabled the selection of fifteen antagonists which promoted greater inhibition of mycelial growth at fourteen days after the treatment, varying from 53,54% to 90,41% of inhibition. In the seed rice health test, Bonança variety, a greater incidence of Curvularia oryzae (70 %) and a lower incidence of Fusarium sp. (1,6 %) were observed. The seed microbiolization in vitro with Bacillus spp. enabled reduction in the incidence of Curvularia oryzae and Aspergillus niger. Curvularia oryzae, Penicilium sp. and Scopulariopsis sp. control in vivo was greater at seven days after the seed treatment. To the fungi Aspergillus niger and Aspergillus flavus the reduction was greater at fourteen days after the seed treatment.